Análise do Processo de Expansão de uma Empresa Familiar à Luz da Teoria da Estruturação - Netto, Ivo Odilon Barbosa (2021)
The subject of this research approachs a family business and its characteristics present during an expansion process using the theory of structuring to understand all this developement. The study aims to analyze, from the use of the structuring theory, if there were changes made by the subjects in the structure of the family organization due to the introduction of the professionalization of the business, which occurred due to expansion. The research question is how is the structure of a particular family business in an expansion process changed as a result of the interactions of the social agents present in it? I took, then, the case study, descriptive and explanatory, with the qualitative approach. For data collection, semi-structures and documentary analysis interviews were used from June 2019 to December 2020. Subjects from various hierarchical levels were interviewed, from the administrative assistant and manager, to most of the organization's corporate staff, and employees who were before, during and after the expansion process. Those interviews were only carried out after signing the document delivered for the formalization of the documents, either for the purpose of confidentialness of those involved or for the security of the interviewer and the respondent. The company studied in this master degree paper belongs to the food industry and its resides in the region of Grande Vitória/ES. For data analysis, content inspection was used according to Bardin (1977). The theoretical reference is composed mainly by the family company literature the theory of structuring, having as main reference the works of Padula (2000); Gersick et al. (2006); Lodi (1978); Giddens (1989) and Junquilho (2003). In the analysis, data coding and the framing of 15 constructive categories were made, based on the characteristics of the family business, the interaction of the duality of the structure and the processes implemented with the expansion of the organization. It was concluded in the company studied that the agents who participated in the organization, during and after professionalization, were one of the elements responsible for the changes present in the final structure of the organization, thus showing the ability to direct the structure of the company, from its cognoscitive activities, to its finais configuration with formal and formal characteristics still in the organization's processes.